AL-AF’ĀL AL-INJĀZIYYAH DALAM NOVEL ACHBABTUKA AKTSARA MIN MĀ YANBAGHĪ KARYA ‘ASĪR ‘ABDULLĀH AN-NIMSYĪ: KAJIAN PRAGMATIK - Jawat Nur, Abdul (Arabic Letters and Department, 2016)
This paper will discuss al-afâ€™Äl al-injÄziyyah or illocutionary speech acts in a novel Achbabtuka Aktsara Min MÄ YanbaghÄ« as work 'AsÄ«r â€˜AbdullÄh an-NimsyÄ« based on the study of pragmatics. Al-afâ€™Äl al-injÄziyyah in the novel that need to be investigated as it includes expressions that use illocutionary speech acts. Three methods were used in this study, the method of data collection, data analysis methods, and methods of reporting the results of the data analysis. Based on research that has been conducted, concluded that the novel Achbabtuka Aktsara Min MÄ YanbaghÄ«Â by 'AsÄ«r â€˜AbdullÄh an-NimsyÄ«Â (2014)Â use of various kinds of al-afâ€™Äl al-injÄziyyahÂ or illocutionary speech acts. These al-afâ€™Äl al-injÄziyyahÂ are (1) al-ikhbÄriyyah (assertive), (2) al-injÄziyyahÂ (declarative), (3) al-iltizÄmiyyah (commissive), (4) at-taâ€™bÄ«riyyah (expressive), and (5) at-taujÄ«hiyyÄt (directive). Among the five kinds of illocutionary speech acts are the most widely used in novel Achbabtuka Aktsara Min MÄ YanbaghÄ« is a directive speech act or at-taujÄ«hiyyÄt.